Euthanasia between waloons and Flemings: applications and effects of permissive legislation - Freitas, Márcia Araújo Sabino de (Journal of Health Law, 2013)
The article aims at analyzing the social effects, especially in the practice of health professionals, of a permissive legislation to euthanasia, based on Belgian law. After a study of each provision of the law, it was made bibliographic research in PubMed/Medline database, to refer to empirical studies on aspects of Belgian law and provide concrete dimension of its practical effects. Although Belgium and Brazil are culturally different, which would certainly interfere with the social effectiveness of the law, it is possible to refl ect on the results and get notes for Brazil, which has no rule permitting euthanasia. The article also brings a brief overview of Belgium and some terminological notions from bioethics.